Sistem Pendukung Keputusan Menentukan Kinerja Aparatur Kecamatan Di Kantor Camat Galang Dengan Menggunakan Metode AHP - Sri Wahyu Ningsih; Sulindawaty (Sisfokomtek, 2020)
The State Civil Apparatus is always required to have full loyalty and obedience in carrying out its duties. Decision support systems can be used as a solution to a problem or for an opportunity. AHP method is a method that can help solve complex problems by structuring a hierarchy of criteria. Based on this research, the researcher tries to prove the previous research and improve the accuracy of the data so that the researcher takes the title